ANALISIS KEAMANAN PERUSAHAAN SESUDAH PENERAPAN UNDANG-UNDANG KAWASAN TANPA ROKOK PADA INDUSTRI ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - R.Gatot Heru Pranjoto (Kompetensi (Competence : Journal of Management Studies), 2014)
The focus of this research is the security level of the cigarette industry in Indonesia, which is listed on the Indonesia Stock Efe five years after the Law on Non-Smoking Area , while the sample of the research firm selected by purposive sampling , the cigarette industry is listed on the Indonesia Stock Exchange ( IDX ) per 1 January 2008 to December 31, 2012 , which publishes its financial statements every year for 5 years . The purpose of this study was to determine the security level of the cigarette industry in Indonesia After Implementation Act Non-Smoking Area .From the results of the analysis indicate that the value of Z score that is safe cigarette industry is PT HM Sampoerna Tbk and PT Gudang Garam Tbk , because it has a Z Score values from 2008 to 2012 , over 3 , PT Bentoel International Tbk was classified as not bankrupt but not safe , because it has a Z score values fluctuate between 1.81 to 3 , while the tobacco industry 's financial performance shows that the company's ability to meet short- term kewajibaqn memadahi , enterprise effectiveness in using resources well enough , but for Bentoel International Tbk PT needs to be improved . Profitability cigarette industry listed on the Stock Exchange Act after Smoking Zone has increased .